Capacidades e competências das empresas familiares no processo de internacionalização - Moraes, Lucas Marques (2023)
Recent studies show great interest in understanding how family businesses internationalize; however, there is a lack of studies that seek to understand how they use their capabilities and competencies to succeed in the internationalization process. The family's presence within the organization influences the routine, processes, objectives, and paths to search for new markets. Therefore, this Master’s thesis will consist of two articles. The first presents a systematic review of the literature, identifying the main capabilities and competencies used in the internationalization of family businesses that are addressed in the studies. The second will seek to understand how these main capabilities and competencies are used, as well as the role of the family in this construction, through a qualitative study using semi-structured interviews as a collection tool. Therefore, this study contributes by identifying which capabilities and competencies are used by family businesses during the internationalization process, how they are related to the idiosyncratic characteristics of these companies, and how export maturity differentiates the creation and use of specific capabilities and competencies. It is suggested that future research contribute to understanding the micro-foundations that exist in the construction of capabilities and competencies and that can verify whether the findings of these studies converge in different contexts.